2010
DOI: 10.1099/jmm.0.022475-0
|View full text |Cite
|
Sign up to set email alerts
|

Commensal Escherichia coli of healthy humans: a reservoir for antibiotic-resistance determinants

Abstract: This study examined in detail the population structure of Escherichia coli from healthy adults with respect to the prevalence of antibiotic resistance and specific resistance determinants. E. coli isolated from the faeces of 20 healthy adults not recently exposed to antibiotics was tested for resistance to ten antibiotics and for carriage of integrons and resistance determinants using PCR. Strain diversity was assessed using biochemical and molecular criteria. E. coli was present in 19 subjects at levels rangi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
141
2
6

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 191 publications
(162 citation statements)
references
References 48 publications
13
141
2
6
Order By: Relevance
“…UPEC is classified primarily into the pathogenic phylogenetic group B2 and to a lesser extent group D [38]. Although our study revealed the dominance of group A in commensal isolates, group B2, which carries more virulence factors than strains belonging to phylogroups A, B1 and D [39,40], was also found in high proportion (43 %); this was also observed by Bailey et al [41]. A similar frequency was found for commensal E. coli strains from healthy American women and Swedish infants [40,42], although other studies showed that strains from phylogenetic groups A and B1 are the most common [43,44].…”
Section: Phylogenetic Typing Of Upec and Commensal E Colisupporting
confidence: 67%
“…UPEC is classified primarily into the pathogenic phylogenetic group B2 and to a lesser extent group D [38]. Although our study revealed the dominance of group A in commensal isolates, group B2, which carries more virulence factors than strains belonging to phylogroups A, B1 and D [39,40], was also found in high proportion (43 %); this was also observed by Bailey et al [41]. A similar frequency was found for commensal E. coli strains from healthy American women and Swedish infants [40,42], although other studies showed that strains from phylogenetic groups A and B1 are the most common [43,44].…”
Section: Phylogenetic Typing Of Upec and Commensal E Colisupporting
confidence: 67%
“…This antibiotic resistance profile was previously detected in healthy individuals by Bartoloni et al (1998) in Bolivia, van de Mortel et al (1998) in Venezuela and Okeke et al (2000) in Ile-ife, Nigeria. These data are also consistent with the finding of further studies that showed a great antibiotic resistance pattern recorded by the commensal E. coli from lowresource settings (Bailey et al, 2010).…”
Section: Discussionsupporting
confidence: 81%
“…Non-detection of group B2 strains in this study may be due to differences in geographical locations and temporal variation as well as specific features of the population. Moreover, it could also be attributed to the enormous diverse pool of E. coli species (Bailey et al, 2010), or the bacterial characteristics in different topographical arena under the influence of antibiotics usage or the host genetic factor (Duriez et al, 2001). …”
Section: Discussionmentioning
confidence: 99%